Temporal disturbance of a model stream ecosystem by high microbial diversity from treated wastewater. Issue 2 (14th March 2023) - Stach, Tom L.; Sieber, Guido; Shah, Manan; Simon, Sophie A.; Soares, André; Bornemann, Till L. V.; Plewka, Julia; Künkel, Julian; Becker, Christian; Meyer, Folker; Boenigk, Jens; Probst, Alexander J.
Abstract: Microbial communities in freshwater streams play an essential role in ecosystem functioning via biogeochemical cycling. Yet, the impacts of treated wastewater influx into stream ecosystems on microbial strain diversity remain mostly unexplored. Here, we coupled full‐length 16S ribosomal RNA gene Nanopore sequencing and strain‐resolved metagenomics to investigate the impact of treated wastewater on a mesocosm system (AquaFlow) run with restored river water. Over 10 days, community Bray–Curtis dissimilarities between treated and control mesocosm decreased (0.57 ± 0.058 to 0.26 ± 0.046) based on ribosomal protein S3 gene clustering, finally converging to nearly identical communities. Similarly, strain‐resolved metagenomics revealed a high diversity of bacteria and viruses after the introduction of treated wastewater; these microbes also decreased over time resulting in the same strain clusters in control and treatment at the end of the experiment. Specifically, 39.2% of viral strains detected in all samples were present after the introduction of treated wastewater only. Although bacteria present at low abundance in the treated wastewater introduced additional antibiotic resistance genes, signals of naturally occurring ARG‐encoding organisms resembled the resistome at the endpoint. Our results suggest that the previously stressed freshwater stream and its microbial community are resilient to a substantial introduction of treated wastewater. Abstract : Wastewater represents a substantial portion of river microbiomes worldwide, yet its effect on stream microbiomes remains challenging to study. Here, we use a mesocosm setup combined with strain‐resolved metagenomics to unravel the impacts of treated wastewater on previously stressed stream water. The disturbance resulted in a significant shift of the microbiome, which did not persist over 10 days, suggesting that previously stressed stream microbiomes are resilient to the introduction of treated wastewater.